PENERAPAN PROSES KOGNITIF DAN TERAPI COGNITIVE BLOCKING DALAM PENINGKATAN KUALITAS PEMBELAJARAN MENULIS - Sibarani, Berlin (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
Students in general have difficulty in expressing their ideas in writing.This indicates that the teaching of writing is not yet successful. The lack of successis due to, among others, the dominance of theoretical explanation and discussionof how to develop good paragraphs and how to use punctuation correctly in classesof writing. Such teaching behavior may be urged by an underlying belief thatknowledge of writing and mastery of the language used are the main factorsdetermining writing ability. But current research results indicate that writing is acognitive process greatly determined by the thinking or reasoning ability. So theprocess of writing will be hindered when the process of reasoning experiences adead end or cognitive blocking. On the other hand, a reasoning process which runswell produces ideas which then demand expression. The pressure for expressionurges the owner of the ideas to study good language use and how to express ideas inan organized way. Therefore, the teaching of writing had better focus on improvingthinking quality and minimizing cognitive blocking.Keywords: the teaching of writing, cognitive blocking